Analyzing Pronunciation In The Speaking Skill Of Street Vendors In Tourism Area - Jupilatun Jupilatun; M. Junaidi Marzuki; Siti Maysuroh (Journal on Education, 2024)
This study aims to analyze the pronunciation of street vendors in the tourism area using the IELST Speaking descriptor. Pronunciation is vital in tourism as it facilitates successful communication between visitors and locals. Accurate pronunciation enables a traveler to travel to a strange city successfully. a research question was developed to guide the study: the pronunciation level of street vendors in tourist areas is measured by speaking IELST band descriptions. The research results were determined using qualitative descriptive methods. Interviews were employed to collect data. It was designed as a dialogue and monologue. The data was analyzed by table analysis with 9 participants from different backgrounds of education, such as graduated from elementary, junior, and senior high school or no educational background. The results showed that the pronunciation level of street vendors is "limited," with some of them receiving band 6, around 4 people, and criteria "limited," which is more, approximately 5 people. The lack of language training facilities was one of the issues. As a result, providing specialist English language instruction geared toward the tourism context is a viable solution to this problem.